Playing through the pain: The prevalence of perceived shoulder dysfunction in uninjured rugby players using the Rugby Shoulder Score. (March 2022) - Partner, Richard; Jones, Ben; Tee, Jason; Francis, Peter
Abstract: Objective: This study aimed to investigate the prevalence of self-reported shoulder dysfunction using the Rugby Shoulder Score (RSS) reported in arbitrary units (AU) of rugby players available for match selection (uninjured). Design: Cross-sectional survey. Methods: Paper survey at the mid-point of the season of uninjured players (n = 86 males (mean age (±SD): 26 ± 6.9y) from 8 squads (professional n = 34; amateur; n = 52)), using the RSS, subjective impact on rugby performance and previous shoulder injury, analysed using a Mann-Whitney U test. Results: 55% of players reported a level of RSS dysfunction despite being uninjured. Players who also reported their shoulder was impacting on performance had significantly higher median RSS (61, IQR 28AU, p = 0.02) than those who reported no impact on performance (40, IQR 22AU). Conclusions : Findings from this study show that over half of players were playing with a level of self-reported shoulder dysfunction. This figure is higher in the professional game, for those with a history of previous injury and for forwards. Highlights: 55% of players reported a level of RSS dysfunction despite being uninjured. Professionals and forwards reported higher RSS than amateurs and backs. Players with a previous shoulder injury reported higher RSS than those without.